Sosialisasi Bahaya Narkoba Bagi Anak Muda - Yudhy Sanjaya; Manahan Uji Simanjuntak; Go Heeng; Susilo Susanto; Ervi Johan Lo; Josanti Josanti; Agiana Her Visnhu Ditakristi (Sekolah Tinggi Teologi Real Batam, 2021)
The danger of drugs is very real where this is very troubling among teachers or lecturers from educational institutions. Many young people are victimized and if left unchecked it will damage the younger generation which will certainly threaten the life of the nation in the future. Prevention needs to be done. The influence of the use of these prohibited substances can harm the user both for the health of the body and ruster and mental. It can even lead to death. There needs to be an effort to find out why drug use is actually a lot among the younger generation or students. Therefore, this journal was compiled with the hope that it can be a driver for many parties to make efforts to prevent drug use through socialization among young people.AbstrakBahaya narkoba merupakan hal yang sangat nyata dimana ini sangat meresahkan kalangan termasuk guru atau dosen dari instansi pendidikan. Banyak anak muda yang menjdai korban dan bila dibiarkan maka akan merusak generasi muda yang pastinya akan mengancam kehidupan bangsa kedepannya. Pencegahan perlu dilakukan. Pengaruh penggunaan zat terlarang tersebut dapat memberbahayakan penggunanya baik bagi kesehatan tubuh maupun karater dan mental. Bahkan dapat menyebabkan kematian. Perlu adanya upaya mencari tahu mengapa penggunaan narkoba justru banyak dikalangan generasi muda atau para pelajar. Untuk itulah jurnal ini disusun dengan harapan dapat menjadi pendorong banyak pihak untuk melakukan upaya pencegahan penggunaan narkoba melalui sosialisasi di kalangan anak muda.